2012
DOI: 10.1085/jgp.201110738
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum Ca2+ permeation explored from the lumen side in mdx muscle fibers under voltage control

Abstract: Under resting conditions, external Ca2+ is known to enter skeletal muscle cells, whereas Ca2+ stored in the sarcoplasmic reticulum (SR) leaks into the cytosol. The nature of the pathways involved in the sarcolemmal Ca2+ entry and in the SR Ca2+ leak is still a matter of debate, but several lines of evidence suggest that these Ca2+ fluxes are up-regulated in Duchenne muscular dystrophy. We investigated here SR calcium permeation at resting potential and in response to depolarization in voltage-controlled skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…Indeed, it sets the steady‐state Ca 2+ level within the SR lumen, thus conditioning the magnitude of depolarization‐induced SR Ca 2+ release upon muscle activation, but also influencing store‐operated sarcolemmal Ca 2+ entry and cytosolic Ca 2+ resting level. In a physiopathological perspective, it is proposed that an elevated SR Ca 2+ leak may contribute to the development of muscular dystrophies (Bellinger et al 2009; Robin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it sets the steady‐state Ca 2+ level within the SR lumen, thus conditioning the magnitude of depolarization‐induced SR Ca 2+ release upon muscle activation, but also influencing store‐operated sarcolemmal Ca 2+ entry and cytosolic Ca 2+ resting level. In a physiopathological perspective, it is proposed that an elevated SR Ca 2+ leak may contribute to the development of muscular dystrophies (Bellinger et al 2009; Robin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies have shown that fluo‐5N can be used as a relevant Ca 2+ indicator to monitor Ca 2+ changes in the SR lumen of mouse skeletal muscle fibres (Ziman et al 2010; Robin et al 2012). It has also been shown that this indicator is well suited for measuring SR Ca 2+ efflux and the resulting depletion at controlled resting membrane potentials (Robin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that combined treatment of BTS and CPA prevented p38γ phosphorylation suggests that activation of the p38γ isoform but not p38α/β isoforms of MAPK could be highly dependent on changes in energetic demand since both major ATPases active in skeletal muscle during contraction were being inhibited. By extension, p38γ cannot be activated by changes in cytosolic calcium because CPA treatment results in large increases in cytosolic calcium (as shown in frog (Même et al, 1998) and murine muscle fibers (Robin et al, 2012) as well as evidenced by the mechanics data in Figure 4), yet muscle treated with both CPA and BTS have no increase in the p38γ signal.…”
Section: Resultsmentioning
confidence: 88%
“…Stimulating muscle in the presence of BTS alone, which eliminates force production but allows normal calcium transients to proceed, had no effect on the phosphorylation of any of the p38 isoforms when compared to just stimulation alone, confirming a previous report that force production is not responsible for the activation of p38 signaling (Dentel et al, 2005). However, when CPA and BTS were used together, a combination that leads to an increase in intracellular calcium (Robin et al, 2012) but may eliminate up to 97% of the free energy used in exercised muscle (Rall, 1982; Rall, 1985), the increase in p38γ phosphorylation typically found with stimulation was blunted. This demonstrates that p38 MAPK γ is not activated by increased contractile force or intracellular calcium concentration, but instead is responsive to changes in the balance of ATP usage since blocking ATPases also blunts phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation